2009
DOI: 10.1525/sop.2009.52.1.23
|View full text |Cite
|
Sign up to set email alerts
|

In God We Trust: Images of God and Trust in the United States among the Highly Religious

Abstract: In this analysis, the authors use Greeley's "religion as poetry" model to frame an analysis of images of God and trust among the highly religious. Using the 2005 Baylor Religion Survey, the authors regress four ordinal measures of social trust on two images of God measures and a bank of religion and demographic controls. The authors find that having a loving image of God creates greater levels of trust in all four measures among the highly religious. They also find that having an image of God as angry creates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 41 publications
5
70
1
Order By: Relevance
“…However, because of the limitation of the data, the current study could not use a probe nor measure the number of Muslim friends. 3 Previous scholarship has used different and more detailed questions than what this study used to measure the image of God who is angry and judgmental (Froese and Bader 2007;Froese, Bader, and Smith 2008;Mencken, Bader, and Embry 2009). Respondents in other studies were asked how well the adjectives ''critical,'' ''punishing,'' ''severe,'' and ''wrathful'' describe God, out of which an index was made.…”
Section: Data and Measuresmentioning
confidence: 99%
“…However, because of the limitation of the data, the current study could not use a probe nor measure the number of Muslim friends. 3 Previous scholarship has used different and more detailed questions than what this study used to measure the image of God who is angry and judgmental (Froese and Bader 2007;Froese, Bader, and Smith 2008;Mencken, Bader, and Embry 2009). Respondents in other studies were asked how well the adjectives ''critical,'' ''punishing,'' ''severe,'' and ''wrathful'' describe God, out of which an index was made.…”
Section: Data and Measuresmentioning
confidence: 99%
“…Both images appear to be related to the belonging dimension of religiosity and also play a role in non-religious behaviors and attitudes. Mencken et al (2009) find a judgmental image of God to be significantly related to the distrust of neighbors, coworkers, atheists, and people in general, while find that God's judgment is also related to intolerant attitudes toward atheists, homosexuals, racists, and communists. Mencken et al (2009) find a judgmental image of God to be significantly related to the distrust of neighbors, coworkers, atheists, and people in general, while find that God's judgment is also related to intolerant attitudes toward atheists, homosexuals, racists, and communists.…”
Section: Images Of Godmentioning
confidence: 73%
“…A growing body of research has found conceptions of God to be related to a variety of religious and non-religious behaviors and beliefs (Greeley , 1993Ozorak 2003;Bader and Froese 2005;Unnever et al 2005a, b;Bader 2007, 2008;Mencken et al 2009). In assessing the relation between these two dimensions, we have conceptualized God imagery as a manifestation of religious belief and public and private religious practice as indicators of religious behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, mothers and adult children who have similar beliefs may share experiences such as attending church together and have fewer conflicts over religion directly. Second, religious beliefs often guide attitudes and behaviors beyond those directly related to religion (Leege and Kellstedt 1993; Mencken, Bader, and Embry 2009; Sherkat and Ellison 1999), therefore shared religious beliefs would serve to enhance relationship quality by minimizing violations of both family and societal norms and creating fewer disruptions within mother-child relationships. Although this is likely the case in all families, the elevated importance of religion in Black communities (Barnes 2005; Patillo-McCoy 1998) may make this particularly important for Black mothers and their adult children.…”
Section: Discussionmentioning
confidence: 99%